Police and Law Enforcement of Domestic Violence Crimes Based on Human Rights in Indonesia - Iwan Hertanto; Supanto Suparto; Muhammad Rustamaji; Yusuf Saefudin (UIN Sunan Gunung Djati, 2024)
Domestic Violence (DV) as a form of crime that violates the rights of victims cannot be underestimated, the Police as law enforcement officers must be able to enforce the law fairly and beneficially for the integrity and peace of the household. Domestic violence crimes have a serious impact on family continuity and can even threaten the integrity of a family. This crime can occur at any time and happen to anyone, both men and women, but the majority of domestic violence victims are women. Women and children, as the majority of victims of domestic violence, have attracted international attention. The Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) regulates the scope of human rights and the state's obligation to ensure their fulfillment. This normative juridical method research aims to answer why the Police in law enforcement of domestic violence in Indonesia must be based on human rights, through several approaches such as the statutory approach and theoretical approach so that it can be concluded that domestic violence is a criminal offense between the perpetrator and the victim has a close relationship within the scope of the household. Indonesia as a state of law must uphold human rights. Pancasila as the spirit in resolving criminal acts of domestic violence has values that complement each other and qualify between one precept and another and each precept has human rights values. The fundamental values of Pancasila have created a harmonious life in a divine, humane, united, populist, and just manner, this of course has upheld the values of human rights in domestic violence law enforcement by the Police in Indonesia.Â Keywords: domestic violence, police, law enforcement, human rights